Pengaruh Budaya Organisasi dan Komunikasi Terhadap Produktivitas Kerja Karyawan pada PT Gudang Garam Bima - Putra, Indrafit; Kusumayadi, Firmansyah; Hidayanti, Mawar (Universitas Serambi Mekkah, 2024)
This research aims to determine the significant influence of organizational culture and communication on employee work productivity at PT. Bima Salt Warehouse. The research instrument used a questionnaire with a Likert scale. The population in the study were all employees at PT. Gudag Garam Bima, namely 40 respondents consisting of 30 permanent employees and 10 non-permanent employees. The sample in this study was 30 employees with permanent employee status with the sampling technique used, namely purposive sampling. Data collection techniques use observation, questionnaires, documentation. Data analysis techniques use validity tests, reliability tests, multiple linear regression tests, classical assumption tests, correlation coefficient tests, coefficient of determination, t tests and f tests with the help of SPSS version 23 for Windows. The research results show that there is a simultaneous positive and significant influence of organizational culture and communication on employee work productivity at PT. Bima Salt Warehouse.